Is it necessary to "be" a feminist to "make" feminist cinema? Icíar Bollaín and her cinematographic representation of gender. - Cabrera Campoy, Julia (Investigaciones Feministas (Feminist Research), 2017)
Inequality between men and women in cinema has remained stable from its beginnings. Both behind the cameras and on-screen representation, women have been systematically invisible, underrepresented and objectified. Feminist efforts arose in the 1970s to visualize and subvert the existing power order, working through two axes: the critique on patriarchy and patriarchal cinema industry, and the development of feminist counter-cinema. Despite their efforts, women's situation has not been greatly improved. However, from the 90s a stream of female authors considered feminists by the critic disowning feminism has spread out. Their films are led by strong capable women, no longer representing women's struggles but assuming their victories and creating from them. New categories of analysis such as post-feminist cinema have been developed for those films. Nevertheless, I question whether these are essentially feminist representations since they are building alternative models of femininity. If they are, does this mean that a feminist consciousness is not necessary to make feminist films? In order to address this question I analyze gender representation in Bollaín’s filmography, and see whether their films fit in any feminist category despite her denial to the term, and the implication this could have.
Keywords: Feminist film theory; Counter-cinema; Post-feminist cinema; Postmodernism; Icíar Bollaín